Challenges of living a multidimensional working model for social workers - Hutchison, Elizabeth D.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2007)
Helping students to think multi-dimensionally and to apply behavioural science knowledge to the world of social work practice, this book also provides emphasis for students on issues of diversity and populations-at-risk.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Social service -- Practice; Social problems; Electronic books